2014
DOI: 10.1111/jocn.12703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nurses' perceptions of the impact of targeted depression education and a screening and referral tool in an acute cardiac setting

Abstract: Much complexity lies in caring for cardiac patients with depression, including issues such as misdiagnosis. Targeted education, including use of appropriate instruments, has the potential to facilitate early recognition of the signs and symptoms of depression in the acute cardiac setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…A multitude of models or frameworks were developed for health services quality improvements such as Donabedian (9) and more recently (4) . Since Donabedian framework is already largely used in nursing studies to evaluate quality of care (12)(13) , this model was chosen to analyze the retained studies.…”
Section: Studies Included In Qualitative Synthesis N=36mentioning
confidence: 99%
“…A multitude of models or frameworks were developed for health services quality improvements such as Donabedian (9) and more recently (4) . Since Donabedian framework is already largely used in nursing studies to evaluate quality of care (12)(13) , this model was chosen to analyze the retained studies.…”
Section: Studies Included In Qualitative Synthesis N=36mentioning
confidence: 99%
“…Sanders also evaluated depression screening practices and factors associated with depression screening in a population of CNMs and observed a positive correlation of three factors associated with likelihood of screening for depression: attitude, perceived ability, and knowledge [15]. Ski and colleagues evaluated the impact of a training workshop on the implementation of a departmental screening policy and found that participating cardiac ward nurses were more aware of the prevalence of depression among cardiac patients and more confident about their ability to successfully identify patients at increased risk for depression [16]. Although Sowden et al reported a positive response among cardiac care nurses to a departmental screening policy over a 12-month period, many hospitals do not include routine depression screening as part of their care protocols and the decision to screen is left to the discretion of individual nurses [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that cardiac health professionals feel inadequately skilled to support patients in their emotional recovery 4 and need education about the identification and management of anxiety and depression in the cardiac setting. 22,23 The cardiac blues online training programme directly addresses this need and gap. The present study demonstrates that the training goes some way towards equipping health professionals with the required skills to support patients in their emotional Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that health professionals need education about the identification and management of anxiety and depression in the cardiac setting. 22,23 To date, there has been a paucity of resources available for either patients or health professionals to support patients' emotional recovery.…”
Section: Introductionmentioning
confidence: 99%